State Control over Water Resources: PDAM Makassar and the Irony of Article 33 of the 1945 Constitution - Tandori; Caritas, Woro Murdiati (Fakultas Hukum Universitas Widya Mataram, 2025)
The clean water crisis that has persisted for more than two decades in Makassar City reflects a systemic failure in the implementation of clean water supply policies, despite the SPAM Law and its derivative regulations. This study uses a normative juridical approach to analyze the effectiveness of legal norms and the reality of clean water access in Makassar, with indicators including conformity with the 1945 Constitution and international human rights, central-local division of authority, and guarantee of sustainability of water supply. The findings indicate overlapping and disharmonized regulations, as well as weak policy implementation at the local level, especially in the context of Makassar's PDAM. This study emphasizes the importance of regulatory harmonization, strengthening local capacity, and public participation. This research contributes to the development of water policies that are equitable and responsive to the needs of vulnerable communities, and enriches the discourse on legal effectiveness in the context of decentralization and the right to water.